Воспитното значење на Светиклиментовите слова и поуки - Aneta Jovkovska (Православен богословски факултет, Скопје, 2018)
The Value of Edification in St. Clement’s Homilies and Instructive Writings The writings of the great Slavic master, Saint Clement of Ohrid, evidently do not address strictly defined pedagogical problems. His contemplations, explanations, and instructions on edification are aimed at clarification of the process of edification in the spirit of Orthodox Christianity. St. Clement’s sermons remain faithful to the central task of the Christian edification, which is the call to communion with God. He strived to transform the human reason through the personal experience of faith. His writings exhibit an instructive and affective example of a true Christian edifying mission, an authentic school of Christian thought and wisdom.
International Conference „St. Clement of Ohrid: Clemency in the Bible and in the Church“ /меѓународна конференција „Св. Климент Охридски: милоста и милосрдието во Библијата и во Црквата“ (Охрид, 20-22. 10. 2016)
Keywords: Christian edification, aim and means of Christian edification, Christian mission, care, virtues, salvation, communion with God